A tributação ambiental sobre os veículos automotores na União Europeia: um modelo para o Mercosul - Ferreira, Luiza Lourdes Pinheiro Leal Nunes (2015)
Environmental degradation caused by the lack of preservationists environmental policies coupled with the relentless pursuit of economic growth remains outdated, giving way to the need for preservation of the environment and the pursuit of sustainable development. In this context, the environmental tax is included as an economic instrument available to the State to achieve environmental preservation. Environmental tax on motor vehicles left behind the basis for calculating the tax on the market value of the vehicle, innovating in taxation of these vehicles, using as a basis for calculating the amount of pollutant emissions that release into the atmosphere. An old remodeled with tax calculation basis, in order to protect the environment, fundamental human right recognized internationally. The use of environmental taxes to induce desirable behavior and environmentally friendly, is part of environmental public policies put into practice, especially in the European Union. This study addresses in particular the environmental tax on motor vehicles in environmental policies in the European Union and Mercosur.